Standardization of the Distributed Ledger Technology cybersecurity stack for power and energy applications - Gourisetti, Sri Nikhil Gupta; Cali, Ümit; Choo, Kim-Kwang Raymond; Escobar, Elizabeth; Gorog, Christopher; Lee, Annabelle; Lima, Claudio; Mylrea, Michael; Pasetti, Marco; Rahimi, Farrokh; Reddi, Ramesh; Sani, Abubakar Sadiq (Sustainable Energy, Grids and Networks, 2021)
The global trend toward integration of distributed energy resources is opening doors to advanced, complex, and distributed marketplaces. Such advanced ecosystems, where utility-owned and non utility-owned assets can contribute toward grid operations, generally require distributed communication and grid architectures. We posit the potential of using Distributed Ledger Technologies (DLTs) in supporting such applications, although their full potential has not been fully used, for example in designing long-term scalable solutions in operational technology applications. This is partly due to the lack of standardization across and between different DLTs, as well as other supporting building blocks (e.g., communication protocols). This paper attempts to address this gap by proposing a DLT cybersecurity stack specifically designed for researchers, DLT technology developers, and end users (such as utilities). The DLT cybersecurity stack has been notionally mapped to related cybersecurity components, namely the Open Systems Interconnection (OSI) model, the Transmission Control Protocol/Internet Protocol (TCP/IP) suite, and existing Smart Grid architecture frameworks. In addition, the paper discusses several cybersecurity implications, and demonstrates the potential uses of the DLT cybersecurity stack through multiple power and energy use cases. It is important to note that the stack can be also applied to the DLT use cases that are outside the power and energy domain. This work was performed by the Cybersecurity Task Force under the IEEE P2418.5 Blockchain for Energy Standard working group that part of the IEEE Power and Energy Society’s Smart Buildings, Loads, and Customer Systems (SBLC) technical committee.